The Creativity of the Early Childhood Education’s Teachers in Creating an Animation Media Web-Based in Koto Tangah Padang - Wirdatul Aini; Setiawati Setiawati; Alim Harun Pamungkas (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2019)
One of the success of the Early Childhood Education Institution in society is based on the teacher’s factor. The problem facing by the Early Childhood Education Institution in the sub-district of Koto Tangah is the lack of the creativity of the teachers to use modern media that will motivate children to play while learning. Until now, Early Childhood Education teachers still use traditional media in the teaching and learning process, when it looks outdated and less able to motivate children in learning. This training aims to help the teachers to be creative Early Childhood Education’s teachers in making an animation learning media Web-based. Through the training of animation learning media Web-based, the teachers can improve their ability in applying various media. Skill training method  in making an animation media-based uses; (1) speech method is used to deliver the material theoretically about the concept of Early Childhood Education and the learning characteristics, (2) discussion method is used by the  Early Childhood Education’s teachers to discuss about how to make an animation media web-based, (3) experiment/ practice method  is used to train the Early Childhood Education’s teachers in having an ability in making an animation media, each teacher tries to create an animation media web-based directly. The subject of this research is the 21 teachers, taken from each delegation of the Early Childhood Education Institution in Koto Tangah, Padang. The result of this research for the community can be described: (1) Early Childhood Education’s teachers comprehend characteristics and learning strategies for early childhood, (2) some of them have already skilled, creative in creating web-based animation learning media. It is suggested to the school to always motivate and facilitate the Early Childhood Education’s teachers in creating a good learning media following the advancement of science and technology. The Early Childhood Education’s teachers are expected to have continuous training to improve their creativity in creating a good and varies learning media.